Chitin and Chitosan. Part I. Properties and production - Marcin H. Struszczyk (Polimery)
A review covering 115 refs. presents an introduction into the chitin and chitosan chemistry. Properties of chitin and chitosan, the methods of their preparation (by means of enzymatic and chemical treatment) have been described.